HELP ASAP ILL GIVE A THANKS AND BRAINLIEST Which combined inequality has the same solution set shown in the graph of x?

–3 x ≥ –1


–3 ≤ x > –1
HELP ASAP ILL GIVE A THANKS AND BRAINLIEST Which combined - 1

Answers

Answer 1
Answer:

Answer:

-3 < x ≤ -1

Step-by-step explanation:

we know that

The solution of the graph is equal to the interval  

All real numbers greater than -3 and less than or equal to -1

so the combined inequality is equal to -3 < x ≤ -1!!!!


Related Questions

The function g(x) = x2 - 10x + 24 is graphed on a coordinate plane. Where will the function cross the x-axis?(-6,0) and (4,0)(-2, 0) and (-12, 0)(4.0) and (6.0)(12, 0) and (2.0)
Write the equation of the given line in standard form y=ax+b:The line containing the midpoints of the legs of a right triangle ABC where A (-5,5), B (1,1) and C (3,4) are the vertices.
Evaluate cos 210° without using a calculator by using ratios in a reference triangle.
One recipe for cereal bars uses 5 cups of cereal and 2 1/2 cups of nuts. A different recipe uses 3 cups of cereal and 1 cup of nuts. Which recipe is more nutty?
1. Use the figure below to answer the questions. Give the coordinates for the original points and the points after the given transformation is performed on the original coordinate.

One week Beth bought 3 apples and 8 pears for $14.50. The next week she bought 6 apples and 4 pears and paid $14. Find the cost of 2 apple and the cost of 1 pear.

Answers

Let us assume the cost of 1 apple = x dollars
Let us also assume the cost of 1 pear = y dollars
Then we can form two equations from the details given in the question. Based on those details the required answer to the question can be easily deduced.
3x + 8y = 14.50
And
6x + 4y = 14
Dividing both sides of the equation by 2 we get
3x + 2y = 7
2y = 7 - 3x
y = (7 - 3x)/2
Putting the value of y from the second equation in the first equation we get
3x + 8y = 14.50
3x + 8[(7 - 3x)/2] = 14.50
3x + 4 (7 - 3x) = 14.50
3x + 28 - 12x = 14.50
- 9x = 14.50 - 28
- 9x = - 13.5
9x = 13.5
x = 13.5/9
   = 1.5
Putting the value of x in the second equation we get
6x + 4y = 14
(6 * 1.5) + 4y = 14
9 + 4y = 14
4y = 14 - 9
4y = 5
y = 5/4
   = 1.25
So we can find from the above deduction that the cost of 1 apple is 1.5 dollars and the cost of 1 pear is 1.25 dollars
Then
Cost of 2 apples = 2 * 1.5 dollars
                           = 3.0 dollars
So the cost of 2 apples is $3 and the cost of 1 pear is $1.25.

Find the quotient by doing long division and show work

Answers